Drivers and barriers of non-residential green building certification in Malaysia - Kunasuntare Purumal,; Azlan Shah Ali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Building sector has the largest potential for significantly reducing greenhouse gas emissions compared to other major emitting sectors. Realising this, the green building revolution is one of the focus of the Government to ensure that appropriate and efficient actions are carried out to mitigate the increasing environmental pollution that causes climate change and face the risks of inexistence. However, currently, there are only a few buildings that have managed to be certified. This paper will add to the body of knowledge by identifying the drivers and barriers of green building certification in Malaysia, examine the relationship of the drivers and barriers in the green building certification decision making and recommend actions that could encourage more key players to obtain green building certification. This research is an Explanatory Research conducted using Sequential Mixed Method design. The data collection process was started with literature review before online questionnaire survey was conducted. After the questionnaire data was analysed, semi structured interview (Qualitative Method) was conducted to validate the questionnaire results and the theoretical framework was revisited. Descriptive analysis result and ranking of the variables was analysed. Then, reliability analysis was conducted before a correlation analysis was performed. Based on the quantitative analysis and qualitative validation, it was concluded that the main drive for owners are reduced cost, and increase in company image, supported by government initiative to reduce the cost incurred, through fiscal incentives. Legislative measures, educate public and tax incentives were ranked highest among all the recommendations, while based on the correlation analysis between the recommendations and number of buildings certified, only reduce certification cost was significantly correlated. However, based on the quantitative analysis and interview result, it can be concluded that instead of just creating more incentives, the government needs to educate the public about the benefits of green building certification, including the existence of incentives available. In addition, some sort of legislative measure such as enactment of laws and policies related to green building certification is needed to encourage more building owners to obtain green building certification.